Projects developed by older adults within the educational field : Analysis of a Program of Permanent Education of University Extension of the UNLP - Ciano, Natalia (2017)
This paper intends to approach the conceptualizations about the permanent education and the contributions of Maria Teresa Sirvent in the different degrees of formality of the educative processes. In light of these contributions, a Permanent Adult Education Program of the University Extension Secretariat of the Faculty of Humanities and Educational Sciences of the National University of La Plata will be analyzed. This analysis has been of interest because of the prevalence of educational projects developed by older adults and within them those developed in what has traditionally been called the “non-formal” educational system.